AN ASSESSMENT OF THE INTENTION TO ACCEPT THE SHARIAH-COMPLIANT CROWDFUNDING MODE OF FINANCING IN BORNO STATE, NIGERIA - Sagir Muhammad Sulaiman; Yusuf Muhammad; Muhammad Abdulaziz Muhammad (Journal of Islamic Monetary Economics and Finance, 2021)
Micro-, small and medium-sized enterprises (MSMEs) face numerous obstacles, such as a lack of funding, which hinder their growth and expansion. They must have access to long-term funding to improve and modernise their operations competitively. This study aims to incorporate Shariah-compliant crowd funding among MSMEs in Borno state in Nigeria. It applies partial least squares structural equation modelling (PLS-SEM) on a sample of 341 MSMEs and recommends the need to educate and enlighten them about the benefits of Islamic crowdfunding. The study also recommends the need to produce guidelines that will help develop a legal and regulatory framework for the incorporation of crowdfunding into corporate financing structures. Finally, it is recommended that religious leaders at various levels organise educational programmes on the importance of Shariah-compliant crowdfunding.